Mediating Colloidal Quantum Dot/Organic Semiconductor Interfaces for Efficient Hybrid Solar Cells. Issue 2 (2nd December 2021) - Kim, Byeongsu; Baek, Se‐Woong; Kim, Changjo; Kim, Junho; Lee, Jung‐Yong
Abstract: Emerging semiconducting materials including colloidal quantum dots (CQDs) and organic molecules have unique photovoltaic properties, and their hybridization can result in synergistic effects for high performance. For realizing the full potential of CQD/organic hybrid devices, controlling interfacial properties between the CQD and organic matter is crucial. Here, the electronic band between the CQD and the polymer layers is carefully modulated by inserting an interfacial layer treated with several types of ligands. The interfacial layer provides a cascading conduction band offset (Δ E C ), and reduces local charge accumulation at CQD/polymer interfaces, thereby suppressing bimolecular recombination; a thin thiol‐treated interfacial layer (≈6 nm) decreases shallow traps, resulting in higher short‐circuit current ( J SC ) and fill factor of hybrid solar cells. Based on these results, a high performance CQD/polymer hybrid solar cell is introduced that demonstrates a power conversion efficiency of 13.74% under AM 1.5 solar illumination. The hybrid device retains more than 90% of its initial performance after 402 days under ambient conditions. Abstract : A new design strategy for exploring colloidal quantum dot (CQD)/polymer interfaces is proposed: an additional interfacial layer is incorporated between the CQD/polymer bilayer structures. The interfacial layer between CQD and polymer reduces the localized charge accumulation, suppressing bimolecular recombination. The optimized hybrid devices show a maximum power conversion efficiency of 13.74% and retains over 90% of its initial performance for 402 days under ambient condition without any treatment.